THE GROWTH OF BRAZILIAN SPINACH (Althernanthera sisso hort) FERTILIZED WITH LIQUID ORGANIC FERTILIZER BIOGAS REACTOR - Setiadi, Claudine Greacia; Sutanto, Haryati Bawole; Madyaningrana, Kukuh (MEDIAGRO, 2024)
Organic fertilizers have begun to be widely used in agriculture as an effort to restore soil productivity. One example of organic fertilizer is liquid organic fertilizer which has been widely applied to support the growth of cultivated plants because of the abundance of sources and benefits. Slurry-based liquid organic fertilizers, especially from human waste, have not been widely used as research. The main raw material of this fertilizer is human waste bio-slurry and the plant that is tested is Brasilian spinach (Althernanthera sisso). This research has the aim of studying the effect of applying liquid organic fertilizer based on biogas reactor slurry on the growth of Brasilian spinach plants (Althernanthera sisso). This research uses true experimental method with various fertilizer treatments, namely positive control (commercial fertilizer), negative control (no fertilizer), and various doses of slurry application, namely 0.1 mL, 0.2 mL, and 0.4 mL. The parameters observed were plant height, number of leaflets, leaf width, root length, fresh weight and dry weight of plants. Data analysis of Brasilian spinach plant growth given liquid organic fertilizer based on biogas reactor slurry was analyzed using the One Way Anova test with the SPSS program. The best results were obtained in the negative control treatment for the parameters of plant height, number of leaves, and leaf width, while the best results were obtained in the second treatment with a dose of 0.2 mL in the parameters of root length, wet weight, and dry weight